The Nature Of The Authority Of The Acting Daily Regional Head In Decision Making Based On Laws And Regulations (Journal of Namibian Studies : History Politics Culture, 2023)
This research will use the type of sociological/empirical (nondoctrinal) legal research. This research is to analyze the existence/existence of the Regional Head Daily Executor  according to the laws and regulations that apply to the government in several districts/cities in Central Sulawesi Province. The research results show that The essence of the existence of the Regional Head's Daily Executor according to the applicable laws and regulations, namely the 1945 Constitution, Law Number 23 of 2014 concerning Regional Government, Law Number 30 of 2014 concerning Government Administration, namely providing justice , legal certainty and expediency. The implementation of the Regional Head's Daily Executor  duties in running the wheels of local government in Central Sulawesi Province, is less effective. The factors that influence the implementation of the Regional Head's Daily Executor tasks in running the wheels of government in the region, namely the legal substance factor and the legal structure factor and the legal culture factor.As recommendations for this study are regulations are needed regarding the implementation of tasks or main tasks and functions of the Regional Head's Daily Executor  in running the wheels of regional government, which are more concrete and clear.